2019
DOI: 10.1098/rsos.190938
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone architecture in the stylopod epiphyses of mustelids (Mammalia, Carnivora)

Abstract: Mustelidae, a carnivoran clade that includes for instance weasels, badgers, otters and martens, has undergone several evolutionary transitions of lifestyle, resulting in specializations for fossorial, natatorial and scansorial locomotion, in addition to more generalized species. The family is therefore regarded as offering an adequate framework for morpho-functional analyses. However, the architecture of the epiphyseal trabecular bone, which is argued to be particularly responsive to the biomechanical environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Previous examinations of several levels of organisation of bone structure, be it histology [70,71], microanatomy (e.g. trabecular architecture [43,50,[72][73][74][75]), or gross morphology [22,23], documented various patterns of correlation with species' phylogenetic relationships, lifestyle, and body size. This work attempts to tease apart these effects with a comparative analysis relying on a sample encompassing multiple convergent acquisitions of the same lifestyle, covering as extensively as possible the body size range within each clade, and using subsets of data when lifestyles significantly differ in the represented species' body size.…”
Section: Methodsmentioning
confidence: 99%
“…Previous examinations of several levels of organisation of bone structure, be it histology [70,71], microanatomy (e.g. trabecular architecture [43,50,[72][73][74][75]), or gross morphology [22,23], documented various patterns of correlation with species' phylogenetic relationships, lifestyle, and body size. This work attempts to tease apart these effects with a comparative analysis relying on a sample encompassing multiple convergent acquisitions of the same lifestyle, covering as extensively as possible the body size range within each clade, and using subsets of data when lifestyles significantly differ in the represented species' body size.…”
Section: Methodsmentioning
confidence: 99%
“…This transformed tree was then used for an rrpp regression with 10,000 permutations. If the recovered lambda was negative or greater than 1, its value was forced to be 0 or 1, respectively (see similar protocol in Amson and Kilbourne [ 167 ]). All p values were adjusted with the Holm method [ 168 ] using the p.adjust function of the built-in stats package.…”
Section: Methodsmentioning
confidence: 99%
“…However, some in vivo works have revealed that diaphyseal internal bone functional adaptation can be more complex than modeled (e.g., Lanyon and Rubin 1985;Judex et al 1997;Demes et al 1998;Wallace et al 2014). Recent analyses of how CSP and trabecular structure have evolved according to ecology using a phylogenetic framework have revealed complex/unexpected adaptative scenarios that can probably be explained by heterogeneous and disparate bone-dependent or trait-dependent models of morphological diversification (e.g., Amson and Kilbourne 2019;Scheidt et al 2019;Parsi-Pour and Kilbourne 2020). It is another element in support of the need to use model-fitting analysis in future studies, as suggested above.…”
Section: Evolvability Of Internal and External Structure In The Humerus And Femurmentioning
confidence: 99%